Implementation of the Student Teams Achievement Divisions Cooperative Learning Model in Improving Learning Outcomes in Islamic Religious Education Subjects in Junior High Schools - Rimah, Rimah; Mawardi, Mawardi (South Sulawesi Education Development (SSED), 2026)
This research aims to improve student learning outcomes in Islamic Religious Education and Ethics at Satap To’Bakkun State Junior High School by applying the Student Teams Achievement Divisions (STAD) cooperative learning model. This study uses the Classroom Action Research method, consisting of planning, implementation, observation, and reflection stages across three cycles. The research subjects were grade VII A students, and data were collected through observation and learning outcome tests. The study found a significant increase in learning outcomes and student activities. The average value of learning outcomes increased from 61.91% in cycle I to 82.26% in cycle II and 87.43% in cycle III. Learning activities also increased from 58.10% in the pre-cycle to 87.92% in the third cycle. These findings suggest that the STAD model is efficacious in improving student learning outcomes and engagement.